PEACE ADVOCACY AND THE BASIS OF BUILDING FOREIGN RELATIONS OF ISLAMIC STATES IN THE QURAN - Hamoda, Mahmoodalnor (ULUL ALBAB Jurnal Studi Islam, 2020)
This study addressed the knowledge of the peace advocacy and building foreign relations of Islamic states in the Holy Quran. Whoever reads the book of Allah almighty may find it full of the vocabulary of peace advocacy, and relations between nations and people. The study included examples mentioned in the Holy Quran showing the need for peace and the foundations of building relations between nations and people. It addressed the meanings of peace advocacy and its importance.Â  It also showed that the peace advocacy and Islam call of prophets and messengers (peace be on them) and the way of the righteous and reformers. The origin in the relationship of Muslims to others is peace and the call to God, not war, and not fighting. Islam is a religion of mercy and happiness for humanity, and it is not spread by the sword, but by proof, argument, wisdom and good preaching. With this peace advocacy and peace that the Quran has guided us to, love and communication will replace hatred and result in intimacy between Muslim and non-Muslim communities. The results of the study showed that the importance of preachers need in this era and save life from evil and sedition. Thus, the society is safe from conflicts, peaceful and reformed.